Potential ergogenic activity of grape juice in runners - Toscano, L. T.; Tavares, R. L.; Toscano, L. T.; da Silva, C. S. O.; de Almeida, A. E. M.; Biasoto, A. C. T.; Gonçalves, M. da C. R.; Silva, A. S. (Applied Physiology, Nutrition, and Metabolism, 2015)
Recent studies have indicated that certain food products have ergogenic potential similar to that of sports supplements. The present study aimed to investigate the potential ergogenic effect of integral purple grape juice on the performance of recreational runners. Twenty-eight volunteers of both sexes (age, 39.8 ± 8.5 years; peak oxygen consumption, 43.2 ± 8.5 mL/(kg·min)) were randomized into either a group that received grape juice (grape juice group (GJG), n = 15; 10 mL/(kg·min) for 28 days) or a group that received an isocaloric, isoglycemic, and isovolumetric control beverage (control group (CG), n = 13). A time-to-exhaustion exercise test, anaerobic threshold test, and aerobic capacity test were performed, together with assessments of markers of oxidative stress, inflammation, immune response, and muscle injury, performed at baseline and 48 h after the supplementation protocol. The GJG showed a significant increase (15.3%) in running time-to-exhaustion (p = 0.002) without significant improvements in either anaerobic threshold (3.6%; p = 0.511) or aerobic capacity (2.2%; p = 0.605). In addition, GJG exhibited significant increases in total antioxidant capacity (38.7%; p = 0.009), vitamin A (11.8%; p = 0.016), and uric acid (28.2%; p = 0.005), whereas a-1-acid glycoprotein significantly decreased (20.2%; p = 0.006) and high-sensitivity C-reactive protein levels remained unchanged. In contrast, no significant changes occurred in any of these variables in the CG. In conclusion, supplementation with purple grape juice shows an ergogenic effect in recreational runners by promoting increased time-to-exhaustion, accompanied by increased antioxidant activity and a possible reduction in inflammatory markers.